Some properties of LP-Sasakian manifolds admitting a quarter symmetric Non Metric Connection - Singh, Jay Prakash
The object of the present paper is to study weakly symmetric, weakly Ricci symmetric, generalized recurrent and generalized Ricci recurrent LP-Sasakian manifolds admitting a quarter symmetric non metric connection ∇.
Keywords: Quarter-symmetric non metric connection; LPSasakian manifolds; Weakly symmetric; Weakly Ricci symmetric; Generalized recurrent